Advances in gene therapy for the treatment of sickle cell anemia - Vázquez, Dania Patricia Alvarez; Barajas, Alejandro Fabricio Aguirre; Chávez, Karla Reyes; Hernández, Maricarmen Aguilar; Ledesma, Kemberly Noemi Zambrano; Barrera, Tane Del Río; Garcia Santiago, Gerardo; Castro, Alejandra Arias (International Journal of Research in Medical Sciences, 2024)
Currently, sickle cell anemia is a β-hemoglobinopathy, meaning a genetic autosomal recessive disease, affecting 400,000 newborns worldwide. Approximately 5% of the global population are carriers of genes causing this pathology. Regarding treatment, there are medical and pharmacological therapies for the disease; however, the only known curative option is allogeneic hematopoietic stem cell transplantation. Nonetheless, there is a high rejection rate, compounded by the fact that it is only available to a limited number of patients. Now, there is a new alternative: gene therapy, which is based on the addition and modification of genes.